Prevalence and risk factors of Epiretinal membranes in a Chinese population: the Kailuan Eye study - Zhu, Xiao Bo; Yang, Mo Chi; Wang, Ya Xing; Qian, Wang; Yan, Yan Ni; Yang, Jing Yan; Wu, Shou Ling; Chen, Shuo Hua; Dong, Li; Wei, Wen Bin; Jonas, Jost B. (Investigative ophthalmology & visual science, 2020)
To investigate the prevalence of epiretinal membranes (ERMs) and their risk factors in a Chinese population. The community-based Kailuan Eye Study included 14,440 participants (9835 male, 4605 female) with a mean age of 54.0 ± 13.3 years (range, 20-110 years). They underwent a systemic and ophthalmologic examination. ERMs were diagnosed on fundus photographs. Retinal photographs assessable for the presence of ERMs were available for 13,295 (92.0%) individuals (9094 male) with a mean age of 53.6 ± 13.3 years (range, 20-110 years). ERMs were found in 1013 participants (1489 eyes) with a prevalence of 7.6% (95% confidence interval [CI], 7.1%-8.1%). Secondary ERMs caused by intraocular reasons were found 46 (4.5%) individuals (69 [4.6%] eyes). A higher prevalence of any ERMs (and of primary ERMs) was associated with older age (odds ratio [OR]: 1.08; 95% CI:1.07-1.10), higher body mass index (OR: 1.05; 95% CI: 1.00-1.11), higher prevalence of smoking (OR:1.43; 95% CI: 1.01-2.03), higher serum concentration of glucose (OR: 1.08; 95% CI: 1.04-1.13), and lower serum concentration of uric acid (OR: 0.99; 95% CI: 0.99-1.00). Visual acuity was significantly (P = 0.002) lower in eyes with premacular fibroses than in eyes with cellophane macular reflexes. In our cross-sectional community-based study, the prevalence of all ERMs was 7.6%. Among the group of participants with ERMs, secondary ERMs caused by intraocular reasons were detected in 46 (4.5%) individuals (69 [4.6%] eyes). A higher prevalence of any ERM and of primary ERMs was associated with older age, higher body mass index, higher prevalence of smoking, a higher serum concentration of glucose, and a lower serum concentration of uric acid.